PMN-PT/PVDF Nanocomposite for High Output Nanogenerator Applications - Chuan Li; Wenbo Luo; Xingzhao Liu; Dong Xu; Kai He (Nanomaterials, 2016)
The 0.7Pb(Mg1/3Nb2/3)O3-0.3PbTiO3(0.7PMN-0.3PT) nanorods were obtained via hydrothermal method with high yield (over 78%). Then, new piezoelectric nanocomposites based on (1−x)Pb(Mg1/3Nb2/3)O3-xPbTiO3 (PMN-PT) nanorods were fabricated by dispersing the 0.7PMN-0.3PT nanorods into piezoelectric poly(vinylidene fluoride) (PVDF) polymer. The mechanical behaviors of the nanocomposites were investigated. The voltage and current generation of PMN-PT/PVDF nanocomposites were also measured. The results showed that the tensile strength, yield strength, and Young’s modulus of nanocomposites were enhanced as compared to that of the pure PVDF. The largest Young’s modulus of 1.71 GPa was found in the samples with 20 wt % nanorod content. The maximum output voltage of 10.3 V and output current of 46 nA were obtained in the samples with 20 wt % nanorod content, which was able to provide a 13-fold larger output voltage and a 4.5-fold larger output current than that of pure PVDF piezoelectric polymer. The current density of PMN-PT/PVDF nanocomposites is 20 nA/cm2. The PMN-PT/PVDF nanocomposites exhibited great potential for flexible self-powered sensing applications.